2015
DOI: 10.1021/acs.biomac.5b01394
|View full text |Cite
|
Sign up to set email alerts
|

Facile Construction of pH- and Redox-Responsive Micelles from a Biodegradable Poly(β-hydroxyl amine) for Drug Delivery

Abstract: Here we demonstrate a type of pH and reduction dual-sensitive biodegradable micelles, which were self-assembled by a cationic polymer in an aqueous solution. Due to tumor cells or tissues showing low pH and high reduction concentration, these micelles possessed specific tumor targetability and maximal drug-release controllability inside tumor cells upon changes in physical and chemical environments, but presented good stability at physiological conditions. CCK-8 assay showed that the DOX-loaded micelles had a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(51 citation statements)
references
References 86 publications
2
49
0
Order By: Relevance
“…[31,32] Among these specific stimuli, redox responsiveness is one of the most enticing one, for example to be exploited in cells and tissue with reducing environments. [11,[33][34][35] Based on the concept of redox responsivity, several studies have reported micellar dissociation in response to dithiothreitol (DTT) or glutathione (GSH) and consequential release of micelle-embedded cargo, such as DNA molecules, [36] doxorubicin, [9][10][11] and siRNA. [31] However, most of the redox-responsive micelles contain the redox responsive disulfide on the edge between the core and the shell; cleavage of the disulfide bonds on the shell does not always lead to a fully disassociated micellar core, which decreases the efficiency of release of the core-embedded molecules.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[31,32] Among these specific stimuli, redox responsiveness is one of the most enticing one, for example to be exploited in cells and tissue with reducing environments. [11,[33][34][35] Based on the concept of redox responsivity, several studies have reported micellar dissociation in response to dithiothreitol (DTT) or glutathione (GSH) and consequential release of micelle-embedded cargo, such as DNA molecules, [36] doxorubicin, [9][10][11] and siRNA. [31] However, most of the redox-responsive micelles contain the redox responsive disulfide on the edge between the core and the shell; cleavage of the disulfide bonds on the shell does not always lead to a fully disassociated micellar core, which decreases the efficiency of release of the core-embedded molecules.…”
Section: Resultsmentioning
confidence: 99%
“…A similar behavior was described in literature for poly-hydroxylamine-based micelles. [11] The disulfide cleavage and reformation can be also observed by the naked eye. After treatment with 6 equivalents of DTT, the solution became partially clear due to the cleavage of disulfide bonds and subsequent disassembly of the micelles.…”
Section: Redox Response Of Ad-ss-ad-based C4msmentioning
confidence: 96%
See 1 more Smart Citation
“…[1][2][3][4][5][6] The release of the payloads from these responsive micelles happens in a controlled manner on arrival at the target site, only when triggered by external stimuli, such as light, temperature, pH, redox potential, enzymes and ionic strength. [7][8][9][10][11][12] Recently, multi-responsive assemblies have been developed to optimize the release of functional species in different environments. Biodegradable multi-segmented polyurethanes (PUs) with stimuli responsive properties have been widely studied as drug carriers due to their good biocompatibilities and tailorable molecular structures.…”
Section: Introductionmentioning
confidence: 99%
“…The aim is to reduce side effects of cytotoxic anticancer drugs, while improving their therapeutic efficiency . A primary requirement for nanomaterials to be used for intended biological applications is their biocompatibility . Various nanomaterials ranging from inorganic nanoparticles (NPs) to polymeric liposomes have been reported as drug carriers .…”
Section: Introductionmentioning
confidence: 99%